The implementation of RME approach using concrete objects media to improve the mathematical connection skill of fifth-grade elementary school students - Hendra Erik Rudyanto; Destia Destia (Universitas Kanjuruhan Malang, 2023)
Mathematical connection skill needs to be mastered. This study aims to determine: 1) implementing a realistic approach to enhance mathematical connection skills using concrete objects as media and 2) improving the mathematical connection skill by applying the Realistic Mathematics Education approach using concrete objects as media in fifth-grade elementary school students. The research subjects consisted of 17 students. The method of this study is Classroom Action Research. The data collection method is by tests, using mathematical connection questions as the instrument. The research results show that in Cycle I, eleven students (64.7%) passed the minimum score, while six students (35.3%) did not, with a classical average of 73.83. In Cycle II, 14 students (82.35%) passed, and three (17.65%) did not, with a classical average of 82.65. These findings indicate that applying the Realistic Mathematics Education (RME) approach with concrete objects as media can improve the mathematical.